An exploratory study of therapeutic misconception among incarcerated clinical trial participants. Issue 1 (2nd January 2016) - Christopher, Paul P.; Stein, Michael D.; Springer, Sandra A.; Rich, Josiah D.; Johnson, Jennifer E.; Lidz, Charles W.
ABSTRACT: Background: Therapeutic misconception, the misunderstanding of differences between research and clinical care, is widely prevalent among non-incarcerated trial participants. However, little attention has been paid to its presence among individuals who participate in research while incarcerated.Methods: This study examined the extent to which 72 incarcerated individuals may experience therapeutic misconception about their participation in one of six clinical trials, and its correlation with participant characteristics and potential influences on research participation.Results: On average, participants endorsed 70% of items suggestive of therapeutic misconception. The tendency toward therapeutic misconception was significantly higher among African Americans and Latinos compared to Whites, among older and less educated participants, and among enrollment in a substance-abuse-related trial; it was also correlated with a belief that the trial was the only way to obtain needed treatment.Conclusions: Therapeutic misconception may be particularly high among select incarcerated individuals and is associated with a perceived lack of treatment options. Further examination of therapeutic misconception among incarcerated research participants is needed.